Respuesta agronómica de frejol de palo (Cajanus cajan L.) con abonos orgánicos. - Cedeño Diéguez, Jorge Luis (2022)
This research was carried out at the SACHA-WIWA Experimental Center, located in the Guasaganda village belonging to La Maná Canton of Cotopaxi Province, and aimed to evaluate the agronomic response of the cultivation of pigeon pea (Cajanus cajan, L.) to the application of organic fertilizers. A Completely Random Block Design (DBCA) was applied which had 4 treatments and 4 repetitions with 4 experimental units, on the other hand, the statistical analysis was performed by means of the DUNCAN multiple range test at 5% statistical probability, the treatments were T1 = Organic fertilizer 5 kg per m2, T2 = Organic fertilizer 6 kg per m2, T3=Organic fertilizer 7 kg per m2 AND T4=Organic fertilizer 8 kg per m2. In the present work, variables were taken, which were: Height of the plant (cm), the diameter of the stem (mm), the number of branches, the nutritional content of organic fertilizer, and the chemical composition of the leaf area of the pigeon pea. Demonstrating that the nutritional content of the fertilizer presents high concentrations of macronutrients with an ideal pH for the cultivation of the pigeon pea. In the agronomic parameters, the height of the plant, number of branches, and diameter of the stem the best was the T3. The nutritional content of the foliage was better in EL T2 in P and K and micronutrients.